Variability in Human-Animal Interaction Research - Rodriguez, Kerri E.; Herzog, Harold; Gee, Nancy R. (Frontiers in Veterinary Science, 2021)
The field of Human-Animal Interaction (HAI) is plagued with mixed results. Some findings appear to indicate that interacting with a companion animal is beneficial for some aspect of human health and wellbeing, while other research outcomes are inconclusive or even indicate the opposite. The purpose of this paper is to take a closer look at this variability in research outcomes and to provide plausible explanations and potential remedies. Some of the reasons for mixed results are likely due to the wide variety of methodologies implemented, intermittent use of standardized measures and manualized protocols, variability in human and animal participants, and limited quantification of human-animal interactions or definitions of pet ownership. Variability in research outcomes is not unique to HAI and is, in fact, not uncommon in many more established fields such as psychology and medicine. However, the potential reasons for the variability may be linked to the unique nature of HAI in that, in its’ simplest form, it involves two complex organisms, a human and a companion animal, interacting in dynamic ways. We argue that this complexity makes research in this field particularly challenging and requires a broad spectrum of theoretical and methodological considerations to improve rigor while ensuring the validity and reliability of conclusions drawn from study results.